A time step reduction method for multi-period optimal power flow problems - Schween, Nils; Meyer-Hübner, Nico; Gerstner, Philipp; Heuveline, Vincent (Preprint series of the Engineering Mathematics and Computing Lab (EMCL), 2019)
The computation of the optimum of a dynamical or multi-period Optimal Power Flow problem assuming an Interior Point Method (IPM) leads to linear systems of equations whose size is proportional to the number of considered time steps. In this preprint we investigate a possibility to reduce the amount of time steps needed to be taken into account: Assuming that the power grid’s dynamic is mainly determined by changes of the residual demand, we drop time steps in case it does not change much. Hence, the size of the linear systems can be reduced. We tested this method for the German Power Grid of the year 2023 and a synthetic 960 h profile. We were able to reduce the amount of time steps by 40% without changing the objective function’s value significantly.